Effect of different final irrigation solutions on push-out bond strength of root canal filling material - R. Rahmatillah; Isyana Erlita; Buyung Maglenda (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: The adhesion of root canal filling material to dentin is one of the crucial factors in determining the success of endodontic treatment. However, the smear layer that forms during instrumentation serves as an interface that impedes the bonding mechanism of the filling material. A proper irrigation solution is required to remove the smear layer and provide a dentin surface that supports the bonding mechanism of the filling material in establishing good adhesion. Purpose: This study aims to evaluate and compare the bond strength of filling material with different final irrigation solutions. Methods: Mandibular premolars were prepared by a crown down, pressure-less technique and divided into three final irrigation groups (2.5% NaOCl, 17% EDTA and 20% citric acid). The root canal of each tooth was obturated using epoxy sealer and gutta-percha. A two-millimetre-thick section of the apical third portion of each group was arranged for the push-out assessment using a universal testing machine in an apical to coronal direction at 1 mm/min crosshead speed. Results: A one-way ANOVA test indicated the difference in push-out bond strength among the groups (p<0.05). A post hoc Bonferroni test presented a statistically significant difference in the bond-strength value between the 2.5% NaOCl group compared with the 20% CA group (p<0.05). Conclusion: The push-out bond strength of root canal filling material is increased by applying a chelating agent as the final irrigation solution where 20% of CA presents the highest push-out bond strength.